EFISIENSI REPRODUKSI SAPI PERANAKAN LIMOUSIN AKSEPTOR INSEMINASI BUATAN DI KECAMATAN TIKUNG, KABUPATEN LAMONGAN TAHUN 2016 - Prastyorini, Vina Ari; Supranianondo, Koesnoto; Safitri, Erma; Restiadi, Tjuk Imam; wurlina, wurlina; Hernawati, Tatik (Ovozoa: Journal of Animal Reproduction, 2018)
The purpose of this study was known the difference of reproductive performans Limousine Cross Breed that haved artificial insemination from diffrence straw from BBIB Singosari and BBIB Lembang covering Conception Rate, Service per Conception, and Calving Rate in period 2016th. This study uses survey research which data from primary and secondary. Primary data were obtained from interview with Limousine Cross Breed breeders and secondary data were obtained from artificial insemination officer's record. The observed variables are Conception rate (CR),  Service per conception (S/C) and Calving rate  (CvR). Data were analyzed descriptive that average and Chi Square.Result of research showed no significant difference (p>0.05) on CR, S/C and CvR between Limousin cross breed cows that haved artificial insemination from BBIB Singosari and BIB Lembang.